Food Processing at a Crossroad - Knorr, Dietrich; Watzke, Heribert (Frontiers in Nutrition, 2019)
Recently processed foods acquired negative connotations in consumer and expert debates about food-health imbalance. Under the appearance of a dietary guideline, a new classification system was proposed to avoid processed foods. However, characterization like “ultra-processing” misguides consumers by suggesting that processing affects the body stronger than nutrients. Food processing played a distinguished role in the development of the human condition undergoing in its 1.9 million year old history a continuous transformation from basic cooking into advanced food technology. While there is a need for understanding effects of processing on nutrition and body, existing nutritional profiling and food descriptor systems are able analyzing the impact of processing. A newly established ISO standard for natural food ingredients sets a starting point for a positive surveying of food technology. During the last 35 years, novel and emerging food technologies provoked a paradigm shift away from conventional process methodologies to gentler, non-thermal processing. This paper attempts to call for a radical change and worldwide adaptation of the key research and development area tackling the grand challenges in our food systems. Using simplifying “black-and-white” classification systems falls short of these goals and abandons ways towards innovative and healthier foods.